The Extensive Relationship Between Eyes and Mind: Understanding the Psychology Behind Your Vision. - Dhakal, Pratyush (Optometry & Visual Performance, 2026)
The perception of sight, commonly regarded as a direct and objective interpretation of reality, is, in fact, a deeply subjective process actively modulated by an individual's psychological state. This article explores the burgeoning field of psychosomatic ophthalmology, which investigates the profound impact of human psychology on visual health and perception. It synthesizes evidence from ophthalmology, neuroscience, and psychology to argue for a holistic, mind-body approach to eye care. The article details the neurobiological pathways through which psychological distress, particularly chronic stress and anxiety, adversely affects ocular health. It elaborates on the role of the hypothalamic-pituitary-adrenal (HPA) axis and the sustained release of cortisol, which can impair blood flow, increase inflammation, and disrupt the blood-retinal barrier. These mechanisms are discussed as contributing factors in the progression of sight-threatening diseases such as glaucoma, age-related macular degeneration (AMD), diabetic retinopathy, and dry eye disease. Furthermore, the review examines how transient emotional states and cognitive processes like attention actively shape visual perception. Evidence is presented demonstrating that mood can alter the perceived saturation of color, while attentional biases, influenced by fears and desires, can change how we interpret visual scenes and even perceive physical space. The influence of stable personality traits, such as neuroticism and optimism, on perceptual biases and long-term visual health outcomes is also considered.